Temporal-mode selection with a Raman quantum memory - Munns, J; Thomas, S; Kaczmarek, K; Ledingham, P; Saunders, D; Nunn, J; Brecht, B; Walmsley, I (Optical Society of America, 2017)
Temporal modes (TMs) of pulsed single-photon states have been identified as appealing basis states for quantum information science. Recent work has seen progress towards TM-selective operations based on nonlinear optics. Here, we demonstrate for the first time a linear TM-selective device, namely a Raman quantum memory in warm atomic Caesium vapour. We achieve switching fidelities of 86.5% when operating the memory with ns-duration pulses. These results pave the way towards new quantum information applications, where TM-selection, TM-reshaping, and network synchronisation are achieved with one single device.